SHIRT SALES SYSTEM APPLICATIONS IN THE COMMUNITY BONAN N 'DAVE USING VISUAL FOXPRO 9.0. - Veronika Ayu S; Marzuki, Skom, MMSI Marzuki, Skom, MMSI (Jurnal Sistem Informasi, 2010)
By looking at the rapid growth of the world where many a community that usescomputer technology as a means of supporting a business success in the appropriatefields with expertise. The process of data input was done manually is no longerrelevant, the problems that often arise when handled manually, among others,problems in collecting data, making reports and price calculation, if it is donemanually, there may be a mistake and will take time in search of data. One way is tocreate a sales system, which using this system we can more easily and more quicklyin the calculation of prices, the search data and create reports.